Do judokas present differences between upper limbs for the concentric strength of the internal and external rotators of the shoulder? - Aedo-Muñoz, E.; Brito, C. J.; Muñoz, P. M.; Nóbrega, O. D. T.; Miarka, B.; Valenzuela, M. G.; Arriagada-Tarifeño, D. (Isokinetics and Exercise Science, 2024)
BACKGROUND: Long-time judo training can lead athletes to develop upper limb asymmetry and shoulder asymmetry during force production, mainly in the action of pulling, pushing, and throwing; that requires higher strength and velocity of the internal and external rotators of the shoulders, which may also result in shoulder injury, or a decrease in judo performance. OBJECTIVE: To investigate asymmetries in concentric force of the internal and external shoulder rotators of the dominant and non-dominant upper limbs in high-level judokas at angular velocities of 60, 180, and 300°/s. METHODS: 14 highly trained male judokas (age 24.4 ± 4.8 yrs.; body mass 87.9 ± 18.7 kg; height 1.8 ± 0.1 m). All participants performed 5 attempts of movement concentric internal and external rotation of the shoulder with 3 angular velocities (60°/s, 180°/s, and 300°/s) in an isokinetic dynamometer (Cybex® Humac Norm Dynamometer CSMI, model 502140). The data were analyzed by independent t-student (discrete analysis) a statistical parametric mapping (SPM) curve (one-dimensional analysis). There was no difference in dominant vs. non-dominant for discrete analysis (p> 0.05). There was no difference in dominant vs. non-dominant for SPM analysis. None of the comparisons surpassed the comparison cut-off (tcrit) for the t-test (p> 0.05). CONCLUSIONS: Based on results, judokas do not present significant asymmetries in concentric force of external or internal shoulder rotators when compared to the dominant vs. the non-dominant upper limb according to discrete and one-dimensional (SPM) analysis.